A wear-resistant and corrosion-resistant polyvinyl chloride cable material

By mixing and processing materials such as polyvinyl chloride resin, wear-resistant and corrosion-resistant polyvinyl chloride cable materials are prepared, which solves the problem of insufficient wear and corrosion resistance of existing cable materials in complex environments, and achieves a longer service life and better chemical stability.

CN118725483BActive Publication Date: 2025-05-02JIANGSU SHUANGDENG POWER TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410941294.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2025-05-02
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

The existing polyvinyl chloride cable materials have insufficient wear resistance and corrosion resistance in highly corrosive environments or frequent friction occasions, making it difficult to meet the needs of complex environments, resulting in a shortening of the service life of the cable.

Method used

The polyvinyl chloride resin, performance enhancement filler, plasticizer, stabilizer, light calcium carbonate, antioxidant and paraffin are mixed evenly, and the wear-resistant and corrosion-resistant polyvinyl chloride cable material is obtained by extrusion molding and granulation through extruder.

Benefits of technology

It significantly improves the wear resistance of cable materials, reduces friction resistance, extends service life, and maintains excellent corrosion resistance in acid-base corrosive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of cable materials, and in particular to a wear-resistant and corrosion-resistant polyvinyl chloride cable material, which is used to solve the problem that traditional polyvinyl chloride cable materials are insufficient in wear resistance and corrosion resistance and are difficult to meet the use requirements in complex environments; the polyvinyl chloride cable material significantly improves the wear resistance of the cable material by adding performance-enhancing fillers, and reduces the friction resistance of the cable in the extrusion molding process, so that the cable is not easily damaged when it is worn by external forces, and the service life of the cable is extended, and the cable material can also have excellent corrosion resistance and can be used for a long time in an acid and alkali corrosive environment without being damaged; the cable material of the invention not only has excellent wear resistance and corrosion resistance, but also maintains the original electrical properties and processing properties of the polyvinyl chloride cable material, and meets various use requirements of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cable materials, in particular to a wear-resistant and corrosion-resistant polyvinyl chloride cable material. Background Art

[0002] With the rapid development of industries such as electricity and communications, cables, as important carriers of power and information transmission, have increasingly higher performance requirements. Although the polyvinyl chloride cable materials on the market currently have good insulation and processing properties, they are deficient in wear resistance and corrosion resistance, which results in insufficient wear resistance and corrosion resistance in certain special environments, such as highly corrosive environments or occasions of frequent friction. It is difficult to meet the use requirements in complex environments, resulting in a shortened service life of the cable. Therefore, the development of a polyvinyl chloride cable material with excellent wear resistance and corrosion resistance is of great significance to improving the overall performance of the cable. Summary of the invention

[0003] In order to overcome the above-mentioned technical problems, the object of the present invention is to provide a wear-resistant and corrosion-resistant polyvinyl chloride cable material: by uniformly mixing polyvinyl chloride resin, performance enhancing filler, plasticizer, stabilizer, light calcium carbonate, antioxidant and paraffin to obtain a mixed material, extruding the mixed material through an extruder, and granulating to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material, thereby solving the problem that traditional polyvinyl chloride cable materials are insufficient in wear resistance and corrosion resistance and are difficult to meet the use requirements in complex environments.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A wear-resistant and corrosion-resistant polyvinyl chloride cable material comprises the following components in parts by weight:

[0006] 100-120 parts of polyvinyl chloride resin, 11-23 parts of performance enhancing filler, 4-8 parts of plasticizer, 1-5 parts of stabilizer, 10-16 parts of light calcium carbonate, 0.5-1.5 parts of antioxidant and 1.5-4.5 parts of paraffin;

[0007] Wherein, the wear-resistant and corrosion-resistant polyvinyl chloride cable material is prepared by the following steps:

[0008] Step 1: uniformly mixing polyvinyl chloride resin, performance enhancing filler, plasticizer, stabilizer, light calcium carbonate, antioxidant and paraffin to obtain a mixed material;

[0009] Step 2: Extruding the mixed material through an extruder and granulating it to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material.

[0010] As a further solution of the present invention: the performance enhancing filler is prepared by the following steps:

[0011] Step s1: 4-nitrotrifluorotoluene and anhydrous methanol are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction for 20-25 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min. Then, liquid bromine is added dropwise while stirring, and the dropping rate is controlled to be 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 4-5 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain intermediate 1;

[0012] Step s2: Add intermediate 1, 10% palladium carbon and anhydrous ethanol to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, stir and react for 20-25 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add hydrazine hydrate solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 8-10 hours. After the reaction is completed, the reaction product is filtered while hot, the filtrate is added to ice water, and then allowed to stand to precipitate, and then vacuum filtered, the filter cake is placed in a vacuum drying oven, and dried at a temperature of 50-60°C for 2-3 hours to obtain intermediate 2;

[0013] Step s3: Add intermediate 2, anhydrous potassium carbonate and chloroform to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, stir and react for 30-40 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add allyl bromide dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 4-5 hours. After the reaction is completed, the reaction product is added to a hydrochloric acid solution to precipitate, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 50-60°C for 2-3 hours to obtain intermediate 3;

[0014] Step s4: Add intermediate 3, 1H,1H-pentafluoropropanol, anhydrous potassium carbonate and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat the mixture to reflux and continue stirring the reaction for 6-8 hours. After the reaction is completed, cool the reaction product to room temperature, add it to distilled water, and then extract it with dichloromethane for 2-3 times. Combine the extracts and dry them with anhydrous magnesium sulfate. Then vacuum filter and rotary evaporate the filtrate to remove the solvent to obtain intermediate 4.

[0015] Step s5: Add intermediate 4, γ-mercaptopropyltrimethoxysilane, azobisisobutyronitrile and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 80-90°C and continue stirring and reacting for 4-5 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain a pellet modifier;

[0016] Step s6: Add chromium trioxide, pellet modifier and ethanol solution to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then raise the temperature to 70-75°C and continue stirring and reacting for 6-8 hours. After the reaction is completed, cool the reaction product to room temperature and then centrifuge it. Wash the precipitate with anhydrous ethanol and distilled water for 3-5 times in turn, then place it in a vacuum drying oven and dry it at a temperature of 60-70°C for 3-5 hours to obtain a performance-enhanced filler.

[0017] As a further embodiment of the present invention: the plasticizer is one of di(2-ethylhexyl) phthalate, dibutyl phthalate and diethyl phthalate.

[0018] As a further embodiment of the present invention: the stabilizer is one of magnesium stearate, calcium stearate and aluminum stearate.

[0019] As a further solution of the present invention: the antioxidant is one of antioxidant 168, antioxidant 264 and antioxidant 1010.

[0020] As a further solution of the present invention: the usage ratio of the 4-nitrotrifluorotoluene, anhydrous methanol and liquid bromine in step s1 is 10 mmol: 50-60 mL: 25-30 mmol.

[0021] As a further solution of the present invention: the usage ratio of the intermediate 1, 10% palladium carbon, anhydrous ethanol and hydrazine hydrate solution in step s2 is 10 mmol: 0.12-0.18 g: 50-60 mL: 15-25 mL.

[0022] As a further solution of the present invention: the mass fraction of the hydrazine hydrate solution in step s2 is 65-70%.

[0023] As a further solution of the present invention: the usage ratio of the intermediate 2, anhydrous potassium carbonate, chloroform and allyl bromide in step s3 is 10 mmol: 13-15 mmol: 60-70 mL: 11-13 mmol.

[0024] As a further solution of the present invention: the mass fraction of the hydrochloric acid solution in step s3 is 8-10%.

[0025] As a further scheme of the present invention: the usage ratio of the intermediate 3, 1H,1H-pentafluoropropanol, anhydrous potassium carbonate and N,N-dimethylformamide in step s4 is 10 mmol: 22-25 mmol: 30-35 mmol: 100-120 mL.

[0026] As a further solution of the present invention: the usage ratio of the intermediate 4, γ-mercaptopropyltrimethoxysilane, azobisisobutyronitrile and N,N-dimethylformamide in step s5 is 10 mmol: 11-13 mmol: 0.01-0.03 g: 100-120 mL.

[0027] As a further solution of the present invention: the usage ratio of the chromium trioxide, the pellet modifier and the ethanol solution in step s6 is 10g:0.8-4.0g:100-120mL.

[0028] As a further solution of the present invention: the volume fraction of the ethanol solution in step s6 is 80-85%.

[0029] Beneficial effects of the present invention:

[0030] The invention discloses a wear-resistant and corrosion-resistant polyvinyl chloride cable material. The polyvinyl chloride resin, a performance-enhancing filler, a plasticizer, a stabilizer, light calcium carbonate, an antioxidant and paraffin are uniformly mixed to obtain a mixed material, the mixed material is extruded and formed by an extruder, and granulated to obtain the wear-resistant and corrosion-resistant polyvinyl chloride cable material. The performance-enhancing filler is added to the polyvinyl chloride cable material, so that the wear resistance of the cable material is significantly improved, and the friction resistance of the cable in the extrusion molding process is reduced, so that the cable is not easily damaged when being worn by external forces, and the service life of the cable is extended. The cable material can also have excellent corrosion resistance and can be used for a long time in an acidic and alkaline corrosive environment without being damaged. The cable material of the invention not only has excellent wear resistance and corrosion resistance, but also maintains the original electrical properties and processing properties of the polyvinyl chloride cable material, and meets various use requirements of the cable.

[0031] The invention discloses a wear-resistant and corrosion-resistant polyvinyl chloride cable material. In the process of preparing the polyvinyl chloride cable material, a performance-enhancing filler is firstly prepared. Firstly, 4-nitrobenzotrifluoromethane and liquid bromine are reacted to introduce bromine atoms into the benzene ring of 4-nitrobenzotrifluoromethane to obtain intermediate 1. Then, intermediate 1 is reacted with hydrazine hydrate solution, and the hydrazine hydrate solution reduces the nitro group on intermediate 1 to amino group to obtain intermediate 2. Then, intermediate 2 is reacted with allyl bromide, and the amino group on intermediate 2 reacts with the bromine atom on allyl bromide to introduce alkenyl group to obtain intermediate 3. Then, intermediate 3 is reacted with 1H,1H-pentafluoropropanol, and the bromine atom on intermediate 3 reacts with the hydroxyl group on 1H,1H-pentafluoropropanol to introduce a large number of CF bonds to obtain intermediate 4. Then, intermediate 4 is reacted with gamma-mercaptopropyltrimethoxysilane, and the alkenyl group on intermediate 4 reacts with the mercapto group on gamma-mercaptopropyltrimethoxysilane. A chemical reaction is carried out to introduce a siloxane group to obtain a pellet modifier, and then the pellet modifier is used to treat chromium trioxide to obtain a performance-enhanced filler; the performance-enhanced filler is a composite structure of chromium trioxide coated with an organic substance, and chromium trioxide has excellent properties of high hardness, thermal stability and low friction coefficient. Adding it to a polyvinyl chloride cable material can give it excellent wear resistance. After the pellet modifier treats the chromium trioxide, its dispersion performance can be improved, so that it can be evenly distributed in the polyvinyl chloride cable material, and the performance improvement effect is better. In addition, the molecular structure of the pellet modifier contains a large number of CF bonds, and the CF bonds have large bond energy, high stability, and low surface energy, showing good lubricity, thereby reducing its friction coefficient, greatly improving its wear resistance, and also making it have good chemical resistance, improving its corrosion resistance, so that it can still maintain an excellent state for a long time in harsh environments. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1:

[0034] This embodiment is a method for preparing a wear-resistant and corrosion-resistant polyvinyl chloride cable material, comprising the following steps:

[0035] Step S1: 10 mmol 4-nitrotrifluorotoluene and 50 mL anhydrous methanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then 25 mmol liquid bromine was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 1;

[0036] Step S2: 10 mmol of intermediate 1, 0.12 g of 10% palladium carbon and 50 mL of anhydrous ethanol were added to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then 15 mL of a 65% hydrazine hydrate solution was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was filtered while hot, the filtrate was added to ice water, and then allowed to stand to precipitate, and then vacuum filtered, the filter cake was placed in a vacuum drying oven, and dried at a temperature of 50° C. for 2 h to obtain intermediate 2;

[0037] Step S3: 10 mmol of intermediate 2, 13 mmol of anhydrous potassium carbonate and 60 mL of chloroform were added to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stirred for 30 min at a temperature of 25 ° C and a stirring rate of 300 r / min, and then 11 mmol of allyl bromide was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was added to a hydrochloric acid solution with a mass fraction of 8% to precipitate, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 50 ° C for 2 h to obtain intermediate 3;

[0038] Step S4: 10mmol of intermediate 3, 22mmol of 1H,1H-pentafluoropropanol, 30mmol of anhydrous potassium carbonate and 100mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25°C and a stirring rate of 300r / min for 20min, and then the temperature was raised to reflux and the stirring reaction was continued for 6h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to distilled water, and then extracted twice with dichloromethane, the extracts were combined and dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate 4;

[0039] Step S5: 10 mmol of intermediate 4, 11 mmol of γ-mercaptopropyltrimethoxysilane, 0.01 g of azobisisobutyronitrile and 100 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture was heated to 80° C. and stirred for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain a pellet modifier;

[0040] Step S6: 10 g of chromium trioxide, 0.8 g of a pellet modifier and 100 mL of an ethanol solution with a volume fraction of 80% are added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then heated to 70° C. and continued to stir for 6 h. After the reaction, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 3 h to obtain a performance-enhanced filler;

[0041] Step S7: weigh 100 parts of polyvinyl chloride resin, 11 parts of performance enhancing filler, 4 parts of plasticizer, 1 part of stabilizer, 10 parts of light calcium carbonate, 0.5 parts of antioxidant and 1.5 parts of paraffin wax according to weight parts, and set aside; the plasticizer is di(2-ethylhexyl) phthalate; the stabilizer is magnesium stearate; the antioxidant is antioxidant 168;

[0042] Step S8: uniformly mixing the polyvinyl chloride resin, the performance enhancing filler, the plasticizer, the stabilizer, the light calcium carbonate, the antioxidant and the paraffin to obtain a mixed material;

[0043] Step S9: Extruding the mixture into a shape through an extruder, and granulating the mixture to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material.

[0044] Embodiment 2:

[0045] This embodiment is a method for preparing a wear-resistant and corrosion-resistant polyvinyl chloride cable material, comprising the following steps:

[0046] Step S1: 10 mmol 4-nitrotrifluorotoluene and 55 mL anhydrous methanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen was introduced for protection. The reaction was stirred for 22 min at a temperature of 28° C. and a stirring rate of 350 r / min. Then, 28 mmol liquid bromine was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 1;

[0047] Step S2: 10 mmol of intermediate 1, 0.15 g of 10% palladium carbon and 55 mL of anhydrous ethanol were added to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 22 min, and then 20 mL of a 68% hydrazine hydrate solution was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the dropwise addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was filtered while hot, the filtrate was added to ice water, and then allowed to stand to precipitate, and then vacuum filtered, the filter cake was placed in a vacuum drying oven, and dried at a temperature of 55° C. for 2.5 h to obtain intermediate 2;

[0048] Step S3: 10 mmol of intermediate 2, 14 mmol of anhydrous potassium carbonate and 65 mL of chloroform were added to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stirred for reaction at a temperature of 28°C and a stirring rate of 350 r / min for 35 min, and then 12 mmol of allyl bromide was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 4.5 h. After the reaction was completed, the reaction product was added to a hydrochloric acid solution with a mass fraction of 9% to precipitate, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 55°C for 2.5 h to obtain intermediate 3;

[0049] Step S4: 10mmol of intermediate 3, 24mmol of 1H,1H-pentafluoropropanol, 32mmol of anhydrous potassium carbonate and 110mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 28°C and a stirring rate of 350r / min for 25min, and then the mixture was heated to reflux and continued to stir for 7h. After the reaction, the reaction product was cooled to room temperature, and then added to distilled water, and then extracted twice with dichloromethane. The extracts were combined and dried over anhydrous magnesium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 4;

[0050] Step S5: 10 mmol of intermediate 4, 12 mmol of γ-mercaptopropyltrimethoxysilane, 0.02 g of azobisisobutyronitrile and 110 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to 85° C. and stirred for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain a pellet modifier;

[0051] Step S6: 10 g of chromium trioxide, 2.4 g of a pellet modifier and 110 mL of an ethanol solution with a volume fraction of 82% were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then heated to 72° C. and continued to stir for reaction for 7 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with anhydrous ethanol and distilled water for 4 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 4 h to obtain a performance-enhanced filler;

[0052] Step S7: 110 parts of polyvinyl chloride resin, 17 parts of performance enhancing filler, 6 parts of plasticizer, 3 parts of stabilizer, 13 parts of light calcium carbonate, 1.0 part of antioxidant and 3.0 parts of paraffin are weighed in parts by weight for later use; the plasticizer is dibutyl phthalate; the stabilizer is calcium stearate; the antioxidant is antioxidant 264;

[0053] Step S8: uniformly mixing the polyvinyl chloride resin, the performance enhancing filler, the plasticizer, the stabilizer, the light calcium carbonate, the antioxidant and the paraffin to obtain a mixed material;

[0054] Step S9: Extruding the mixture into a shape through an extruder, and granulating the mixture to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material.

[0055] Embodiment 3:

[0056] This embodiment is a method for preparing a wear-resistant and corrosion-resistant polyvinyl chloride cable material, comprising the following steps:

[0057] Step S1: 10 mmol 4-nitrotrifluorotoluene and 60 mL anhydrous methanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 25 min, and then 30 mmol liquid bromine was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 1;

[0058] Step S2: 10 mmol of intermediate 1, 0.18 g of 10% palladium carbon and 60 mL of anhydrous ethanol were added to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stirred for 25 min at a temperature of 30 ° C and a stirring rate of 400 r / min, and then 25 mL of a 70% mass fraction of hydrazine hydrate solution was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was filtered while hot, and the filtrate was added to ice water, and then allowed to stand to precipitate, and then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at a temperature of 60 ° C for 3 h to obtain intermediate 2;

[0059] Step S3: 10 mmol of intermediate 2, 15 mmol of anhydrous potassium carbonate and 70 mL of chloroform were added to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stirred for 40 min at a temperature of 30 ° C and a stirring rate of 400 r / min, and then 13 mmol of allyl bromide was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the dropwise addition was completed, the temperature was raised to reflux and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was added to a hydrochloric acid solution with a mass fraction of 10% to precipitate, and then vacuum filtered. The filter cake was placed in a vacuum drying oven and dried at a temperature of 60 ° C for 3 h to obtain intermediate 3;

[0060] Step S4: 10mmol of intermediate 3, 25mmol of 1H,1H-pentafluoropropanol, 35mmol of anhydrous potassium carbonate and 120mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 30°C and a stirring rate of 400r / min for 30min, and then the mixture was heated to reflux and continued to stir for 8h. After the reaction, the reaction product was cooled to room temperature, and then added to distilled water, and then extracted with dichloromethane for 3 times. The extracts were combined and dried over anhydrous magnesium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 4;

[0061] Step S5: 10 mmol of intermediate 4, 13 mmol of γ-mercaptopropyltrimethoxysilane, 0.03 g of azobisisobutyronitrile and 120 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 90° C. and stirred for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain a pellet modifier;

[0062] Step S6: 10 g of chromium trioxide, 4.0 g of a pellet modifier and 120 mL of an ethanol solution with a volume fraction of 85% were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then heated to 75° C. and continued to stir for 8 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with anhydrous ethanol and distilled water for 5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 70° C. for 5 h to obtain a performance-enhanced filler;

[0063] Step S7: 120 parts of polyvinyl chloride resin, 23 parts of performance enhancing filler, 8 parts of plasticizer, 5 parts of stabilizer, 16 parts of light calcium carbonate, 1.5 parts of antioxidant and 4.5 parts of paraffin are weighed in parts by weight for later use; the plasticizer is diethyl phthalate; the stabilizer is aluminum stearate; the antioxidant is antioxidant 1010;

[0064] Step S8: uniformly mixing the polyvinyl chloride resin, the performance enhancing filler, the plasticizer, the stabilizer, the light calcium carbonate, the antioxidant and the paraffin to obtain a mixed material;

[0065] Step S9: Extruding the mixture into a shape through an extruder, and granulating the mixture to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material.

[0066] Comparative Example 1:

[0067] This comparative example is a method for preparing a wear-resistant and corrosion-resistant polyvinyl chloride cable material, comprising the following steps:

[0068] Step S1: weigh 120 parts of polyvinyl chloride resin, 8 parts of plasticizer, 5 parts of stabilizer, 16 parts of light calcium carbonate, 1.5 parts of antioxidant and 4.5 parts of paraffin wax according to weight parts, and set aside; the plasticizer is diethyl phthalate; the stabilizer is aluminum stearate; the antioxidant is antioxidant 1010;

[0069] Step S2: uniformly mixing polyvinyl chloride resin, plasticizer, stabilizer, light calcium carbonate, antioxidant and paraffin to obtain a mixed material;

[0070] Step S3: Extruding the mixture into a shape through an extruder and granulating the mixture to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material.

[0071] Comparative Example 2:

[0072] This comparative example is a method for preparing a wear-resistant and corrosion-resistant polyvinyl chloride cable material, comprising the following steps:

[0073] Step S1: weigh 120 parts of polyvinyl chloride resin, 23 parts of chromium trioxide, 8 parts of plasticizer, 5 parts of stabilizer, 16 parts of light calcium carbonate, 1.5 parts of antioxidant and 4.5 parts of paraffin according to weight parts, and set aside; the plasticizer is diethyl phthalate; the stabilizer is aluminum stearate; the antioxidant is antioxidant 1010;

[0074] Step S2: uniformly mixing polyvinyl chloride resin, chromium oxide, plasticizer, stabilizer, light calcium carbonate, antioxidant and paraffin to obtain a mixed material;

[0075] Step S3: Extruding the mixture into a shape through an extruder and granulating the mixture to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material.

[0076] Comparative Example 3:

[0077] This comparative example is a method for preparing a wear-resistant and corrosion-resistant polyvinyl chloride cable material, comprising the following steps:

[0078] Step S1: weigh 120 parts of polyvinyl chloride resin, 23 parts of pellet modifier, 8 parts of plasticizer, 5 parts of stabilizer, 16 parts of light calcium carbonate, 1.5 parts of antioxidant and 4.5 parts of paraffin wax according to weight parts, and set aside; the plasticizer is diethyl phthalate; the stabilizer is aluminum stearate; the antioxidant is antioxidant 1010;

[0079] Step S2: uniformly mixing polyvinyl chloride resin, pellet modifier, plasticizer, stabilizer, light calcium carbonate, antioxidant and paraffin to obtain a mixed material;

[0080] Step S3: Extruding the mixture into a shape through an extruder and granulating the mixture to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material.

[0081] The polyvinyl chloride cable materials of Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the test methods were as follows:

[0082] Wear resistance test: The polyvinyl chloride cable material is pressed into a disc with a thickness of 30mm and a diameter of 30mm. The disc is dry rubbed for 2 hours at a speed of 200r / min and a load of 196N.

[0083] Corrosion resistance test: The polyvinyl chloride cable material was pressed into a disc with a thickness of 30 mm and a diameter of 30 mm, and the disc was immersed in an acid solution (5wt% H2SO4 solution) and an alkali solution (20wt% NaOH solution) for 500 hours respectively;

[0084] The test results are shown in the following table:

[0085]

[0086] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the addition of chromium trioxide, a pellet modifier and a performance enhancing filler can significantly improve the performance of polyvinyl chloride cable materials, making them have excellent wear resistance and corrosion resistance.

[0087] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0088] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A wear-resistant and corrosion-resistant polyvinyl chloride cable material, characterized in that: It comprises the following components in parts by weight: 100-120 parts of polyvinyl chloride resin, 11-23 parts of performance enhancing filler, 4-8 parts of plasticizer, 1-5 parts of stabilizer, 10-16 parts of light calcium carbonate, 0.5-1.5 parts of antioxidant and 1.5-4.5 parts of paraffin; Wherein, the wear-resistant and corrosion-resistant polyvinyl chloride cable material is prepared by the following steps: Step 1: uniformly mixing polyvinyl chloride resin, performance enhancing filler, plasticizer, stabilizer, light calcium carbonate, antioxidant and paraffin to obtain a mixed material; Step 2: Extruding the mixed material through an extruder, and granulating it to obtain a wear-resistant and corrosion-resistant polyvinyl chloride cable material; Wherein, the performance enhancing filler is prepared by the following steps: Step s1: 4-nitrotrifluorotoluene and anhydrous methanol are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube, a reflux condenser and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction for 20-25 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min. Then, liquid bromine is added dropwise while stirring, and the dropping rate is controlled to be 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 4-5 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain intermediate 1; Step s2: Add intermediate 1, 10% palladium carbon and anhydrous ethanol to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, stir and react for 20-25 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add hydrazine hydrate solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 8-10 hours. After the reaction is completed, the reaction product is filtered while hot, the filtrate is added to ice water, and then allowed to stand to precipitate, and then vacuum filtered, the filter cake is placed in a vacuum drying oven, and dried at a temperature of 50-60°C for 2-3 hours to obtain intermediate 2; Step s3: Add intermediate 2, anhydrous potassium carbonate and chloroform to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, stir and react for 30-40 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add allyl bromide dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to reflux and the stirring reaction is continued for 4-5 hours. After the reaction is completed, the reaction product is added to a hydrochloric acid solution to precipitate, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at a temperature of 50-60°C for 2-3 hours to obtain intermediate 3; Step s4: Add intermediate 3, 1H,1H-pentafluoropropanol, anhydrous potassium carbonate and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat the mixture to reflux and continue stirring the reaction for 6-8 hours. After the reaction is completed, cool the reaction product to room temperature, add it to distilled water, and then extract it with dichloromethane for 2-3 times. Combine the extracts and dry them with anhydrous magnesium sulfate. Then vacuum filter and rotary evaporate the filtrate to remove the solvent to obtain intermediate 4. Step s5: Add intermediate 4, γ-mercaptopropyltrimethoxysilane, azobisisobutyronitrile and N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 80-90°C and continue stirring and reacting for 4-5 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain a pellet modifier; Step s6: Add chromium trioxide, pellet modifier and ethanol solution to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then raise the temperature to 70-75°C and continue stirring and reacting for 6-8 hours. After the reaction is completed, cool the reaction product to room temperature and then centrifuge it. Wash the precipitate with anhydrous ethanol and distilled water for 3-5 times in turn, then place it in a vacuum drying oven and dry it at a temperature of 60-70°C for 3-5 hours to obtain a performance-enhanced filler.

2. A wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The plasticizer is one of di(2-ethylhexyl) phthalate, dibutyl phthalate and diethyl phthalate.

3. The wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The stabilizer is one of magnesium stearate, calcium stearate and aluminum stearate.

4. The wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The antioxidant is one of antioxidant 168 , antioxidant 264 and antioxidant 1010 .

5. The wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The usage ratio of the 4-nitrotrifluorotoluene, anhydrous methanol and liquid bromine in step s1 is 10 mmol: 50-60 mL: 25-30 mmol.

6. The wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The usage ratio of the intermediate 1, 10% palladium carbon, anhydrous ethanol and hydrazine hydrate solution in step s2 is 10mmol: 0.12-0.18g: 50-60mL: 15-25mL; the mass fraction of the hydrazine hydrate solution in step s2 is 65-70%.

7. The wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The usage ratio of the intermediate 2, anhydrous potassium carbonate, chloroform and allyl bromide in step s3 is 10mmol:13-15mmol:60-70mL:11-13mmol; the mass fraction of the hydrochloric acid solution in step s3 is 8-10%.

8. The wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The usage ratio of the intermediate 3, 1H,1H-pentafluoropropanol, anhydrous potassium carbonate and N,N-dimethylformamide in step s4 is 10 mmol: 22-25 mmol: 30-35 mmol: 100-120 mL.

9. The wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The usage ratio of the intermediate 4, γ-mercaptopropyltrimethoxysilane, azobisisobutyronitrile and N,N-dimethylformamide in step s5 is 10 mmol: 11-13 mmol: 0.01-0.03 g: 100-120 mL.

10. The wear-resistant and corrosion-resistant polyvinyl chloride cable material according to claim 1, characterized in that: The usage ratio of the chromium oxide, the pellet modifier and the ethanol solution in step s6 is 10g:0.8-4.0g:100-120mL; the volume fraction of the ethanol solution in step s6 is 80-85%.

Citation Information

Patent Citations

  • Environment-friendly fluorine / silicon-containing heavy anticorrosive epoxy resin paint and preparation method thereof

    CN103450725A

  • Corrosion-resistant and wear-resistant automobile piston ring and processing method thereof

    CN114958100A